Organic Photoredox Carbonylation of Arenediazonium under Mild Conditions - Stuhr, Robin; Jacobi von Wangelin, Axel (Synlett, 2024)
The modular synthesis of diverse carbonyl compounds is at the heart of organic synthesis. An optimized protocol for photoredox carbonylation was developed that operates under milder conditions with mesitylacridinium as a photocatalyst. Arenediazonium salts were converted into benzoates (with alcohols), benzoic acids (with water), benzamides (with amines), and chlorides (with 1-butyl-3-methylimidazolium chloride) at 20 bar CO and 20 °C.
Keywords: photoredox catalysis; carbonylation; carbon monoxide; visible light; arenediazonium compounds; radical reactions